Big Boy 4014 and the steam team : the world's largest steam engine roars back to life! - Arnold, Marsha Diane (Sleeping Bear Press, 2025)
"The story of Big Boy 4014, the world's largest steam locomotive, comes to life--from stranded giant to restored icon to the 150th Golden Spike anniversary, and then onto excursion tours."--